Carcass tissue distribution and characteristics of Small East African and Galla goats, and their F1 crosses to Toggenburg and Anglo-Nubian - OKEYO, A M; WANYOIKE, M M; AHUYA, C O (The Indian Journal of Animal Sciences, 2014)
Pre-slaughter live weights (LW) and carcass characteristics (hot and cold dressed weights (CDW), total lean (TL), total bone (TB), total fat (TF), and fat components such as intestinal fat, subcutaneous fat, empty gut (EG) and other offal weights were determined in 60 females, male and castrated goats of SEA and Galla and their respective F, crosses with Toggenburg and Anglo-Nubian of approximately 3 years of age. Breed group, sex and their first order interactions were tested for relative influence on some of the carcass characteristics. Sex of the animal did not significantly affect the carcass chilling shrinkage (%). However, sex significantly (P